Incarcerated resistance: how identity, gender, and privilege shape the experiences of America's nonviolent activists - Stanger, Anya (Lexington Books, 2022)
Justice action prisoners in the school of the Americas watch and plowshares movements -- Resistance in an imperial state: prison witness -- Like a chiropractic adjustment: aligning actions and beliefs through identity-work -- Embodiment, privilege power, and the experience of action -- Prison communities -- A visitor in someone else's house: the standpoint of justice action prisoners -- Journey through prison witness: the significance of privilege and gender.